PENGARUH METODE TEBAK KATA TERHADAP KEMAMPUAN MENGHAFAL KOSA KATA BAHASA ARAB SISWA MTs PESANTREN DARUL ARQOM MUHAMMADIYAH GOMBARA MAKASSAR - Ilham Ilham; A. Fajriwati Tajuddin (Universitas Muhammadiyah Makassar, 2017)
This study aims to find out the ability to memorize the vocabulary of Arabic language through the application of learning models of words in the pesantren Darul Arqam Gombara. To obtain the accurate data used classroom action research with research data source are all students of MTs Darul Arqam Muhammadiyah Gombara Makassar and Arabic language teacher. Sampling of the population was performed using a random technique. The research instrument used was the initial test (pre-test) and the final test (post-test). Then for data analysis used test of grain validity problem, test of reliability, distinguishing power and level of its difficulty The results of this study could be concluded that 1) The application of guess word method ran well without any obstacle. 2) The ability to memorize vocabulary was improvement, according to the pre-test of the ability to memorize vocabulary with the average value: 51.18 then continued post-test the ability to memorize vocabulary with the average value: 82.66. Thus, it could be concluded that students VIII A MTs Darul Arqam Muhammadiyah Gombara Islamic School Makassar experienced an improvement in the ability to memorize the Arabic vocabulary by using the word guess method. 3) Vocabulary mastery by using the word guess method had increased in spite of not really significant and showed that the using of word guess method gave a positive impact to increase of memorizing ability of students. Keywords: Guess words, memorize, vocabulary, Arabic